Proceedings of the 6th Asia Dengue Summit, June 2023. - Nattachai Srisawat; Duane J Gubler; Tikki Pangestu; Umaporn Limothai; Usa Thisyakorn; Zulkifli Ismail; Daniel Goh; Maria Rosario Capeding; Lulu Bravo; Sutee Yoksan; Terapong Tantawichien; Sri Rezeki Hadinegoro; et al. (Public Library of Science (PLoS), 2024)
The 6th Asia Dengue Summit (ADS) themed "Road Map to Zero Dengue Death" was held in Thailand from 15th-16th June 2023. The summit was hosted by Tropical Medicine Cluster, Chulalongkorn University, Bangkok, Thailand in conjunction with Queen Saovabha Memorial Institute, The Thai Red Cross Society; Faculty of Tropical Medicine, Mahidol University; and the Ministry of Public Health. The 6th ADS was convened by Asia Dengue Voice and Action (ADVA); Global Dengue and Aedes Transmitted Diseases Consortium (GDAC); Southeast Asian Ministers of Education Tropical Medicine and Public Health Network (SEAMEO TROPMED); Fondation Mérieux (FMx) and the International Society for Neglected Tropical Diseases (ISNTD). Dengue experts from academia and research, and representatives from the Ministries of Health, Regional and Global World Health Organization (WHO) and International Vaccine Institute (IVI) participated in the three-day summit. With more than 51 speakers and 451 delegates from over 24 countries, 10 symposiums, and 2 full days, the 6th ADS highlighted the growing threat of dengue and its antigenic evolution, flagged the urgent need to overcome vaccine hesitancy and misinformation crisis, and focused on dengue control policies, newer diagnostics, therapeutics and vaccines, travel-associated dengue, and strategies to improve community involvement.